Perturbed Developmental Serotonin Signaling Affects Prefrontal Catecholaminergic Innervation and Cortical Integrity - Garcia, Lidiane P. (Mol Neurobiol, 2018)
Proper development of the medial prefrontal cortex (mPFC), crucial for correct cognitive functioning, requires projections from, among others, the serotonergic (5-HT) and catecholaminergic systems, but it is unclear how these systems influence each other during development. Here, we describe the parallel development of the 5-HT and catecholaminergic prefrontal projection systems in rat and demonstrate a close engagement of both systems in the proximity of Cajal-Retzius cells. We further show that in the absence of the 5-HT transporter (5-HTT), not only the developing 5-HT but also the catecholaminergic system, including their projections towards the mPFC, are affected. In addition, the layer identity of the mPFC neurons and reelin-positive interneuron number and integration are altered in the absence of the 5-HTT. Together, our data demonstrate a functional interplay between the developing mPFC 5-HT and catecholaminergic systems, and call for a holistic approach in studying neurotransmitter systems-specific developmental consequences for adult behavior, to eventually allow the design of better treatment strategies for neuropsychiatric disorders. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s12035-018-1105-x) contains supplementary material, which is available to authorized users.